2015
DOI: 10.14784/jfrs.53994
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Financial Efficiency Ratios and Stock Prices: An Empirical Investigation on Insurance Companies Listed in Borsa Istanbul

Abstract: It is a common perception that efficiency is an important issue regardless of industry. A sound and highly functional insurance industry serves as a crucial financing channel in an economy. At this aspect, this study aims to examine the relationship between the financial efficiency ratios and stock prices of insurance firms, whose stocks are publicly traded in Borsa Istanbul. The study is performed on quarterly data set. The sample period covers 2005Q1 and 2012Q4. Taking three sets of efficiency ratios, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
1
7
0
1
Order By: Relevance
“…As a result of the analysis, linear relationship was confirmed between NPM and stock prices in all three models. Akyatan (2016), Kaya and Öztürk (2015), Aktaş and Ünal (2015) and also Parlakkaya and Kahraman (2017) reached the similar results. On the other hand, Sevim (2016) revealed that there is no significant relationship between ROA, ROE ratios and stock returns.…”
supporting
confidence: 54%
See 2 more Smart Citations
“…As a result of the analysis, linear relationship was confirmed between NPM and stock prices in all three models. Akyatan (2016), Kaya and Öztürk (2015), Aktaş and Ünal (2015) and also Parlakkaya and Kahraman (2017) reached the similar results. On the other hand, Sevim (2016) revealed that there is no significant relationship between ROA, ROE ratios and stock returns.…”
supporting
confidence: 54%
“…On the other hand, Sevim (2016) revealed that there is no significant relationship between ROA, ROE ratios and stock returns. In addition, Aktaş and Ünal (2015) did their research by using quarterly data. In this study, 1, 2 and 3 months lagged stock prices after each quarter period was taken into consideration.…”
Section: Research Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last period, number of studies give more consideration to efficiency in companies and its relationship with other financial ratios that measure several variables such as firm size (Halkos and Tzeremes, 2007); leverage (Margaritis and Psillaki, 2007;Popova et al, 2017); asset pricing implications (Callice et al, 2019); corporate governance (Lin et al, 2009); profitability (Santosuosso, 2014;Attefah and Polytechnic, 2016;Sunjoko and Arilyn, 2016;Azad et al, 2018); stock prices (Rafet and Seyfettin, 2015;Aktaş and € Unal, 2015); capital Structure (Margaritis and Psillaki, 2007); operational cash flow (Santosuosso, 2014) and effective decision-making (Theogene et al, 2017). Some studies are targeting different sectors such as manufacturing (Alam and Sickles, 1998;Becchetti and Sierra, 2003), insurance (Tana et al, 2009;Greene and Segal, 2004;Cummins and Xie, 2013), agriculture (Selamat and Nasir, 2013) and banking (Rafet and Seyfettin, 2015;Sufian et al, 2016;Theogene et al, 2017). Practically, financial ratios add valuable information that enhance the capability to assess the financial situation of a firm.…”
Section: Introductionmentioning
confidence: 99%
“…Çalışmada kullanılan finansal oranlar şirketlerin likidite, kaldıraç, karlılık durumlarına ilişkin mali oranlar ile etkinlik oranlarından (maliyet etkinliği, gelir etkinliği ve kar etkinliği) oluşmaktadır. Tablo 1' de yer alan analizde kullanılan finansal oranların seçiminde ise sigorta sektörü için yapılan çalışmalardan faydalanılmıştır (Ajlouni & Tobaishat, 2010;Akel ve diğerleri 2017;Akın & Ece, 2013;Aktaş & Ünal, 2015;Altan, 2010;Bülbül & Köse, 2016;Çiftçi, 2004;Dalkılıç, 2012;S. Diacon, 2001;Kayalı, 2007;McDonald & Morris, 1984).…”
Section: çAlışmada Kullanılan Finansal Oranlarunclassified